Systems thinking for the transition to zero pollution - Kirkpatrick,L; Adjiman,C; ApSimon,H; Berry,A; de,Nazelle A; Mijic,A; Myers,R; Woodward,G; Workman,M (Grantham Institute, 2023)
Systems approaches are vital for coordinating decision-making in the face of complex issues because they provide the whole picture view needed to avoid negative unintended consequences and to generate genuine benefits. This paper explains how systems thinking can be used to address environmental pollution and support decision-makers in finding solutions.